Description of the Implementation of Differentiated Learning in the Driving school SMAN 9 Padang on Thermochemical Material Phase F - F, Fina Afrihany; Aini, Faizah Qurrata (Universitas Lampung, 2023)
The purpose of this study was to describe of the implementation of differentiated learning in one of the driving schools in Padang city on thermochemical material. This research includes is descriptive with a quantitative approach. The research data was collected from observation, interviews, and documentation. The sample of this study was one of the XI Phase F chemistry classes consisting of 28 students and the chemistry teacher in the class. The data obtained is processed using the Miles and Huberman interactive model consisting of three stages namely data collection, data reduction and conclusion. The results of the data show that teachers implement differentiated learning on thermochemical material based on student readiness and implemented in the process. The data shows teacher was implemented differentiated learning well on thermochemical material and by the existence of students’ science processes are also good when following differentiated learning. So it can be conclude that the teacher has implemented differentiated learning on thermochemical material well.Keywords: Differentiated Learning, Driving School, ThermochemistryDOI: 10.23960/jppk.v12.i3.2023.15